Th-17 cytokines and interstitial lung involvement in systemic sclerosis. (21st November 2016) - Rolla, G; Fusaro, E; Nicola, S; Bucca, C; Peroni, C; Parisi, S; Cassinis, M C; Ferraris, A; Angelino, F; Heffler, E; Boita, M; Brussino, L
Abstract: The two phenotypes of both limited and diffuse systemic sclerosis (SSc) have different forms of pulmonary involvement: pulmonary arterial hypertension (limited phenotype) or interstitial lung disease (ILD) (diffuse phenotype). We aimed to investigate whether Th17-related cytokines, as measured in exhaled breath condensate (EBC) and in serum were connected to ILD in diffuse SSc patients. We found that for both limited and diffuse SSc, the EBC levels of all cytokines and most of the cytokine serum levels were significantly higher in patients than in controls, while, the EBC levels of Th-17 cytokines and the serum levels of IL-10 and TNF- α were significantly higher in diffuse than in limited SSc. Moreover, the thoracic CT-scan score of ILD was significantly associated with the EBC levels of IL-1 beta and with the serum IL-23, TNF- α and IL-10 levels, whereas lung carbon monoxide diffusing capacity was negatively related to the EBC levels of IL-1 beta, IL-17 and serum IL-10. Serum IL-23 was also inversely correlated with vital capacity. In conclusion, in diffuse SSc patients our results show a clear link between Th-17 cytokines measured both in EBC and in serum with interstitial lung involvement. This highlights how important it is to target Th-17 cytokines when developing new treatments for lung fibrosis.